Adoption Without Optimization: Text Mining and Business Intelligence Analysis on Culinary SME Digital Literacy - Dafitri, Rahma; Daryani, Dian; Sutisna, Entis (Institut Riset dan Publikasi Indonesia, 2026)
Digital transformation has become critical for culinary Micro, Small, and Medium Enterprises (MSME), yet most remain digitally underperforming despite platform adoption, a gap this study terms